Faktor-Faktor Penyebab Kejadian Stunting Pada Balita - K Komalasari; Esti Supriati; Riona Sanjaya; Hikmah Ifayanti (Majalah Kesehatan Indonesia, 2020)
The genesis of stunting is one of the nutritional problems experienced by more than half the stunting children in the world originating from Asia (55 percent) while more than one-third (39 percent) live in Africa. The prevalence of stunting in Indonesia is still high at 29.6 percent. The preliminary studies at Kampung Tulungkakan in 2019 recorded 17.17 percent stunting toddlers. The research objective was to determine the factors that affect the genesis of stunting on a toddler at Kampung Tulungkakan in Bumiratu Nuban Sub-District of Central Lampung Regency 2019. The research type of qualitative is the analytical design and a case-control approach. The population in this research were all toddlers, with a case sample of 28 stunting toddlers and a control sample of 56 toddlers. The analysis used univariate with frequency distribution and bivariate using the chi-square test. The research results showed that the distribution of LBW frequency was 3 toddlers (3.57 percent), non-exclusive breastfeeding status was 49 toddlers (58.33 percent), malnutrition status during pregnancy was 18 mothers (21.43 percent) and 31 primary education mothers (36.90 percent). There is no correlation of LBW with stunting (p-value: 0.743; OR: 1,000. There is an exclusive breastfeeding correlation with stunting (p-value: 0,000; OR: 11,111. There is a correlation between the nutritional status of the mother with stunting (p-value: 0.048; OR: 3.333) the correlation between maternal education and stunting (p-value: 0.046; OR: 2.885) The conclusion of the research is the correlation between the status of exclusive breastfeeding, maternal nutritional status and maternal education with the genesis of stunting while LBW is not related, so it is suggested to health care workers to increase health promotion regarding prevention the genesis of stunting. Abstrak: Kejadian balita pendek (stunting) merupakan salah satu masalah gizi yang dialami lebih dari setengah balita stunting di dunia berasal dari Asia (55 persen) sedangkan lebih dari sepertiganya (39%) tinggal di Afrika. Prevalensi stunting di Indonesia masih tinggi yakni 29,6 persen. Studi pendahuluan di Kampung Tulungkakan tahun 2019 tercatat 17,17 persen balita stunting. Tujuan penelitian untuk mengetahui faktor-faktor yang mempengaruhi Kejadian Stunting pada balita di Kampung Tulungkakan Kecamatan Bumiratu Nuban Kabupaten Lampung Tengah tahun 2019. Jenis penelitian kualitatif dengan desain analitik dan pendekatan case control. Populasi pada penelitian ini adalah keseluruhan balita, dengan sampel kasus sebanyak 28 balita stunting dan sampel kontrol sebanyak 56 balita. Analisis yang digunakan adalah univariat dengan distribusi frekuensi dan bivariat menggunakan uji chi square. Hasil penelitian diketahui distribusi frekuensi BBLR sebanyak 3 balita (3,57 persen), status ASI tidak eksklusif sebanyak 49 balita (58,33 persen), status gizi kurang pada saat hamil sebanyak 18 ibu (21,43 persen) dan pendidikan dasar sebanyak 31 ibu (36,90 persen). Tidak ada hubungan BBLR dengan stunting (p value: 0,743; OR: 1,000. Ada hubungan ASI Eksklusif dengan stunting (p value: 0,000; OR: 11,111. Ada hubungan status gizi ibu dengan stunting (p value: 0,048; OR: 3,333) ADA hubungan pendidikan ibu dengan stunting (p value: 0,046; OR: 2,885). Kesimpulan penelitian ada hubungan status pemberian ASI Eksklusif, status gizi ibu dan pendidikan ibu dengan kejadian stunting sedangkan BBLR tidak berhubungan, sehingga disarankan kepada tenaga kesehatan untuk meningkatkan promosi kesehatan mengenai pencegahan kejadian stunting